Fecho integral de módulos, multiplicidades e poliedros de Newton - Araújo, Amanda Santos (2022)
In this work, we study the integral closure of ideals, Newton polyhedra and Newton non-degenerate ideals. Moreover, we present generalizations of these concepts for modules then, we study the characterization of Newton non-degenerate submodules of On^p. For this we use the Buchsbaum-Rim multiplicity and the mixed multiplicities of ideals. In the Newton non-degenerate case these multiplicities were described by volumes of Newton polyhedra.